Peningkatan Keterampilan Menulis Cerpen Melalui Metode Pengaliran Imaji Berbantuan Media Rekaman Pada Siswa Kelas Xi Smk Sakti Gemolong - Saputri, Tety Permana; , Dra. Main Sufanti, M.Hum (2017)
This research aims to increase student's interest in writing short story and increase students' skill in writing short story in grade XI in Computer and Network Engineering ority, SMK Sakti Gemolong by applying image drift method assist with recording media. Kinds of research, Classroom Action Research (CAR) done in two cycles, in every cycle consist of four components, there are planning, mplementation,research, and reflection. The recording media that used is television advertising of recording.The subject of Classroom Action Research, students grade XI TKJ-B SMK Sakti Gemolong consist of 37 students. The data were obtained through short story writing tests and observation of students' interest in learning process of writing short story. The methods of data collections that used are servation,interview,documentation, field notes, pre-test, and post test. The analysis of data that used is descriptive comparative analysis that comparing the result of observation on achievement values every pre cycle, cylcle I, cycle II.The result of the research showed students' interest in writing short story through image drift method assist with recording media, that shows (1) Interest, from 37,8% to 64,8%, (2) Likes, from 32,4% to 51,35%, (3) Involvement, from 21,6% to 51,35%, and (4) Attention, from 45,9% to 91,89%. The result of short story writing skills through image drift method assist with recording media in grade XI B in Computer and Network Engineering Majority, SMK Sakti Gemolong has increased, that is (1) Pre cycle is about 65,81 (2) Cycle I is about 74,86; and (3) Cycle II is about 81,14. The indicators of short story writing skills are: (1) The contents of short stories, (2) The generic stuctures and presentation, (3) Language, and (4) Mechanics. In conclusion, there is significant result of image drift method assist with recording media in grade XI B in Computer and Network Engineering Majority, SMK Sakti Gemolong.Keywrds : skills, writing, imagination, shadow, short story, interest